2005
DOI: 10.1001/archsurg.140.12.1210
|View full text |Cite
|
Sign up to set email alerts
|

Preexisting Morbidity as an Independent Risk Factor for Perioperative Acute Thromboembolism Syndrome

Abstract: Preexisting morbidities are risk factors for perioperative arterial or venous thromboembolic events and subsequent death within 30 postoperative days.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
1
5

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 44 publications
1
34
1
5
Order By: Relevance
“…5 Prospective studies have been limited because of the low incidence of the event in the noncardiovascular, nonneurosurgical population. 12 Thus, the objective of the current study was to assess the incidence and predictors of perioperative stroke and its role in mortality in a broad range of noncardiac, nonneurosurgical cases using a large, prospectively gathered clinical data set derived from the American College of Surgeons National Surgical Quality Improvement Program (ACS NSQIP).…”
mentioning
confidence: 99%
“…5 Prospective studies have been limited because of the low incidence of the event in the noncardiovascular, nonneurosurgical population. 12 Thus, the objective of the current study was to assess the incidence and predictors of perioperative stroke and its role in mortality in a broad range of noncardiac, nonneurosurgical cases using a large, prospectively gathered clinical data set derived from the American College of Surgeons National Surgical Quality Improvement Program (ACS NSQIP).…”
mentioning
confidence: 99%
“…W dostępnym piśmiennictwie częstość występowania zakrzepicy żył głębokich w otolaryngologii waha się pomiędzy 0,25% a 0,75% [29,92,133,212]. Wśród polskich autorów o zakrzepowym zapaleniu żył głębokich kończyn dolnych piszą Semczuk i wsp.…”
Section: Według Wytycznych Committee On Perioperative Cardiovascular unclassified
“…Na rozwój zakrzepicy żył głębokich wpływają zaburzenia w układzie hemostazy, spowodowane zwolnieniem przepływu krwi, uszkodzeniem śródbłonka naczyniowego oraz wzrostem krzepliwości krwi i spadkiem aktywności fibrynolitycznej osocza [92,115,203].…”
Section: Według Wytycznych Committee On Perioperative Cardiovascular unclassified
See 1 more Smart Citation
“…Perioperative stroke is defined as a brain infarction of ischemic or hemorrhagic etiology that occurs during surgery or within 30 days after surgery [2]. Three of the most consistent risk factors for perioperative stroke identified in the literature are advanced age, renal failure, and a history of stroke or transient ischemic attack [3][4][5][6][7][8]. Mashour et al further identified myocardial infarction within 6 months of surgery, hypertension, history of severe chronic obstructive pulmonary disease, current tobacco use, and a protective effect of Body Mass Index (BMI) of 35-40 kg/m 2 as independent predictors [9].…”
Section: Introductionmentioning
confidence: 99%